Katian (Upper Ordovician) conodonts from Wales. (20th December 2013) - Ferretti, Annalisa; Bergström, Stig M.; Barnes, Christopher R.; Lane, Phil
Abstract Middle and upper Katian conodonts were previously known in the British Isles from relatively small collections obtained from a few localities. The present study is mainly based on 17 samples containing more than 17 000 conodont elements from an approximately 14‐m‐thick succession of the Sholeshook Limestone Formation in a road cut near Whitland, South Wales, that yielded a diverse fauna of more than 40 taxa. It is dominated by representatives of Amorphognathus, Aphelognathus/Plectodina and Eocarniodus along with several coniform taxa. Representatives of Decoriconus, Istorinus and Sagittodontina are reported from the Ordovician of UK for the first time. The fauna is a typical representative of the British Province of the Atlantic Realm and includes a mixture of taxa of North American, Baltoscandic and Mediterranean affinities along with pandemic species. Based on the presence of many elements of Amorphognathus ordovicicus and some morphologically advanced specimens of Amorphognathus superbus, the Sholeshook Limestone Formation is referred to the lower A. ordovicicus Zone. Most of the unit is also coeval with Zone 2 of the Cautleyan Stage in the British regional stage classification, and stage slice Ka3 of the middle Katian Stage in the global stratigraphical classification, an age assignment consistent with data from trilobites, graptolites and chitinozoans. The unusually large collection of M elements of Amorphognathus provides insight into the complex morphological variation in this element of some Katian species of this genus. The Sholeshook conodont fauna is similar to those of the Crûg and Birdshill limestones, but differs in several respects from the slightly older ones from the Caradocian type area in the Welsh Borderland. Although having some species in common, the Sholeshook conodont fauna clearly differs from coeval Baltoscandic faunas and is even more different in composition compared with equivalent North American Midcontinent faunas.